Effect of extrusion on the nutritional value of soybeans and sorghum grain in finishing pigs - G E Fitzner; T L Weeden; Terry L Gugle; Robert H Hines; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1990)
A total of 112 finishing pigs (avg initial wt of 139 lb) was used to determine the effects of adding extruded soybeans and/or sorghum grain to diets for finishing pigs. Treatments were: 1) sorghum-soybean meal control (sorghum-SBM), 2) extruded soybeans and ground sorghum, 3) SBM and extruded sorghum, and 4) extruded soybeans and sorghum. All diets were isocaloric and isolysinic. Using extruded soybeans and/or sorghum improved efficiency of gain compared to the sorghum-SBM control. This response was apparently related to the improved digestibilities of dry matter and nitrogen with the use of extruded ingredients. Optimum digestibility of dry matter and nitrogen was achieved when just the sorghum was extruded, but optimum growth performance (ie., efficiency of gain) was achieved when extruded sorghum and soybeans were added to the diet.; Swine Day, Manhattan, KS, November 15, 1990
Keywords: Swine day; 1990; Kansas Agricultural Experiment Station contribution; no. 91-189-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 610; Swine; GF; Performance; Process; Sorghum